Pulp calcifications in patients with diabetes mellitus - Pilar Araya; Macarena Vega-Marcich; Karla Olivares; Carol Wilhelm; Alain Manuel Chaple Gil; Eduardo Fernández; Mauricio Toro (Editorial Ciencias Médicas, 2020)
Introduction: Dental pulp cells have the capacity to respond to local and systemic stimuli by activating osteopontin, forming pulp calcifications, blocking root canals and modifying internal anatomy, in such a way that they intensify in people with diabetes mellitus. Objective: Determine whether there is a greater presence of calcifications in the pulp chamber of patients with diabetes mellitus vs. patients without diabetes mellitus. Methods: An analytical cross-sectional retrospective case-control study was conducted of medical records and digital periapical radiographs of patients attending undergraduate dental clinics (prosthesis, restoration, comprehensive, periodontics) and graduate dental clinics (periodontics and surgical implantology) of Andrés Bello University, Chile, in the period 2017-2018. A sample was selected of 617 teeth (45 patients) from the clinical database upon applying exclusion and inclusion criteria. The sample was divided into two groups: a case group, formed by 228 undamaged teeth from 22 patients with diabetes mellitus, and a control group, formed by 389 undamaged teeth from 23 patients without diabetes mellitus. Prior calibration was performed by the researchers to identify and classify the pulp calcifications during their radiographic analysis. Chi-squared statistical inferences were made to establish the significance of the results obtained. Results: The teeth from the 22 diabetic patients had more chamber calcifications than the teeth from the 23 nondiabetic patients, for 50% calcified teeth in diabetic patients (n= 114) and 26% in nondiabetic patients (n= 101). This result was statistically significant (p-value< 0.001). Conclusions: Patients with diabetes mellitus were found to be more prone to form chamber calcifications, due to the increase in glucose present in the blood which activates osteopontin.